Investigating the use of analytical procedures by practicing auditors in Wilayah Persekutuan Kuala Lumpur / Ros Norita Abd Samad, Ithnahaini Baharuddin and Anita Che Hassan - Abd Samad, Ros Norita; Baharuddin, Ithnahaini; Che Hassan, Anita (2008)
The purpose of this study is to provide information on the current practice of analytical review procedures within the context of auditing in Malaysia. One hundred and sixteen auditors from Wilayah Persekutuan participated in the survey. The study reveals four important findings. First, the use of judgmental techniques and simple quantitative techniques such as comparison of two points, simple reasonableness test and ratio analysis are preferred compared to advanced quantitative techniques. Second, the use of analytical review procedures are most effective in achieving audit objectives of identifying significant fluctuation in financial statements and assessing overall fairness of presentation. Third, the study also suggests that overall change in the audit approach and increase in professional guidance are the most possible explanation for the increase use of analytical review procedures. Finally, in contrast to prior research, the use of analytical review procedures are more pronounced at substantive stage than planning and final review stage of an audit.